HEALTH EDUCATION HEALTH REPRODUCTION IN ADOLESCENTS AT SMPK SANTU STEFANUS KETANG - Simon, Maria Getrida; N. Nggarang, Bonavantura; Henny Mariati, Lusia; Hepilita, Yohana; Handi, Heribertus (LPPM Univ. Ibn Khaldun Bogor, 2023)
Teeneger is a dynamic development in an individual's life which is characterized by accelerated physical, emotional and social growth. Physical changes that occur are the process of maturation of the genitals, besides that psychological changes also occur. This causes changes in attitudes and behavior, such as attention to appearance, interest in the opposite sex, seeking attention and seeking love, which then lead to sexual desire, because adolescence tends to have a high level of sexuality due to maturity. sex hormones and development of the reproductive organs. This Community Service is carried out to increase the knowledge of teeneger about reproductive health.